PREVENTIVE MEDICAL EXAMINATION OF HEALTHY CHILDREN - Rita R. Kil'diyarova ("Paediatrician" Publishers LLC, 2018)
Preventive medical examinations of healthy children or mass prophylactic examinations of minors in the Russian Federation are governed by the orders of the Ministry of Health of Russia. The data on regulatory and organizational support for the prophylactic examination of healthy children is presented. The article provides a comparative analysis on the frequency of children examinations by a district pediatrician, consultations by specialty doctors as well as additional examinations in accordance with the orders of the Ministry of Health of Russia No.1346n and No.514n entered into force on January 1, 2018. The authors give comments on the proposals of MO Revnova et al. suggested in the article "Towards the Improvement of the System of Mass Prophylactic Examinations of the Child Population".